2007
DOI: 10.1186/1476-4598-6-40
|View full text |Cite
|
Sign up to set email alerts
|

Expression of LIM kinase 1 is associated with reversible G1/S phase arrest, chromosomal instability and prostate cancer

Abstract: Background: LIM kinase 1 (LIMK1), a LIM domain containing serine/threonine kinase, modulates actin dynamics through inactivation of the actin depolymerizing protein cofilin. Recent studies have indicated an important role of LIMK1 in growth and invasion of prostate and breast cancer cells; however, the molecular mechanism whereby LIMK1 induces tumor progression is unknown. In this study, we investigated the effects of ectopic expression of LIMK1 on cellular morphology, cell cycle progression and expression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 41 publications
1
52
1
2
Order By: Relevance
“…To minimize false-positive results, we compared normal and UL tissue taken from the same patients, thus reducing the chances of findings related to polymorphisms and menstrual cycle phases. Our results show that several genes, such as UHRF1, LIMK1, CALD1, MCM3 and others previously correlated with cancer (10)(11)(12), were upregulated in a fraction of the analyzed myomas. However, this fraction of overexpressed genes is very small, indicating that although they may contribute to tumor biology, they are not essential to tumorigenic pathology.…”
Section: Discussionmentioning
confidence: 59%
“…To minimize false-positive results, we compared normal and UL tissue taken from the same patients, thus reducing the chances of findings related to polymorphisms and menstrual cycle phases. Our results show that several genes, such as UHRF1, LIMK1, CALD1, MCM3 and others previously correlated with cancer (10)(11)(12), were upregulated in a fraction of the analyzed myomas. However, this fraction of overexpressed genes is very small, indicating that although they may contribute to tumor biology, they are not essential to tumorigenic pathology.…”
Section: Discussionmentioning
confidence: 59%
“…23 Our recent studies have shown that altered expression of LIMK1 is associated with chromosomal abnormalities and spindle defects. 24 In this study, we identified that the activated (phosphorylated) form of LIMK1/2 was localized in the mitotic apparatus in a mitotic phase-specific manner and that pLIMK1/2 in early phases of mitosis colocalized with g-tubulin. Our results provide novel information on possible association between a LIM motif containing kinase and centrosomal proteins.…”
Section: Introductionmentioning
confidence: 76%
“…The molecular mechanism(s) of how LIMK2 regulates mitosis and its knockdown induces mitotic spindle abnormalities still remains to be determined. Sumi et al (2006), suggested that LIMK2 and LIMK1 are required for spindle organization and chromosome segregation and recent studies have confirmed the role of cofilin phosphorylation by LIMK1 in this process (Davila et al, 2007;Kaji et al, 2008). LIMK2 is localized to the mitotic spindle during metaphase and early anaphase and then redistributed to the spindle midzone and co-localized with midzone microtubules during anaphase and telophase in HeLa cells (Sumi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%